Resenären som aldrig kom fram: Hemlöshet i klassresenärens berättelse - Andersson, Åsa; Kalman, Hildur (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2007)
The articulation of homelessness is a recurrent theme in late 20th century narratives of travels between classes ⁠— whether in academic dissertations, autobiographies or in the literary genre. Travellers of an elder generation not only seem to have arrived, but they also seem to be more content with having travelled. This difference is analysed in terms of subjective class identity ⁠— concerning one's own thoughts and experiences of belonging, and objective class identity ⁠— as defined from a structural perspective and concerned with material factors like income, but also with factors such as status stemming from education and/or profession. We identify the late 20th century traveller's problem of arrival and experience of seemingly impossible class identification with an era marked by political ideas of class struggle. Further, we suggest that having a subjective identity as being of the working class, simultaneously as objectively having travelled between classes, may result in problems concerning the use of power. When being situated in a position of power, the subjective identity might come to work as a rhetorical device, to the extent that it obscures the fact that one both possesses and exercises power.